2016
DOI: 10.1021/acs.iecr.6b00470
|View full text |Cite
|
Sign up to set email alerts
|

Application of Inverse Gas Chromatography for Diffusion Measurements and Evaluation of Fluid Catalytic Cracking Catalysts

Abstract: The diffusion rates of feedstocks and intermediate products in fluid catalytic cracking (FCC) catalysts have relevance for the product selectivities obtained from the conversion of feedstocks in the FCC process. A simple and robust method was developed to determine the diffusion of probe molecules in such catalysts by means of inverse gas chromatography. This procedure is described in detail, and its relevance in FCC is illustrated by several examples. It is shown that catalytic properties of FCC catalysts can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Presented in Fig. 1 are electron micrographs of characteristic FCC particles after synthesis and as extracted from their respective units 36 . Particles of FCC1 measure on average 76 µm in diameter, FCC2 74 µm, and FCC3 91 µm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presented in Fig. 1 are electron micrographs of characteristic FCC particles after synthesis and as extracted from their respective units 36 . Particles of FCC1 measure on average 76 µm in diameter, FCC2 74 µm, and FCC3 91 µm.…”
Section: Resultsmentioning
confidence: 99%
“…Others already suggested that macroscopically measurable structural metrics do not accurately describe the diffusion limitations in or the catalytic performance of FCC particles and that diffusion coefficients, e.g., present a more accurate picture 41 , 42 . Wallenstein et al 36 reported diffusion coefficients in the range 10 −2 –10 −4 cm 2 s −1 , which suggest that intra-particle diffusion in FCC particles occurs predominantly within pores of ~1–80 nm in diameter, the so-called Knudsen regime 43 . Correspondingly, the tomograms presented here register numerous pore throats of the size of voxels within the interconnected pore networks.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion measured by IGC is called transport diffusion and is supported by flow and concentration gradients. 35 It is represented by the diffusion coefficient with units of area per time (e.g., cm 2 /s). The diffusion coefficient is calculated using the van Deemter equation (eq 5) 36 A In eq 5, HETP is the height equivalent to a theoretical plate, A is the eddy diffusion, B is the longitudinal diffusion, C is the mass-transfer resistance in the stationary phase (i.e., packed material), and μ is the average linear velocity of the column flow.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The diffusion measured by IGC is called transport diffusion and is supported by flow and concentration gradients . It is represented by the diffusion coefficient with units of area per time (e.g., cm 2 /s).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation